Simulated microwave propagation delays and atmospheric sky brightness temperatures in the frequency range 14–40 GHz at the Onsala Space Observatory - Forkman, Peter; Flygare, Jonas; Elgered, Gunnar (Chalmers University of Technology, 2021)
The dataset contains time-series of signal propagation delay due to water vapour, liquid water path, and multi-dimensional time-series of atmospheric brightness temperature and transmission, in the frequency range 14 – 40 GHz, at the Onalsa Space Observatory. The simulations are carried out with or without liquid cloud water in the atmosphere. The normalized power-pattern of the antenna is also provided.

We have used atmospheric data from ECMWF and processed them with the open software package ARTS. Details are described in the published paper:
Forkman, P, Flygare, J and Elgered, G (2021).
Water Vapour Radiometry in Geodetic Very Long Baseline Interferometry Telescopes:
Assessed Through Simulations, Journal of Geodesy.

The uploaded readme.txt file gives all the necessary information.
The three data files are saved in the NetCDF format (*.nc)

Data innehåller tidsserier med signalfördröjning på grund av vattenånga och och mängden flytande vatten samt flerdimensionella tidsserier av atmosfärens strålningstemperatur i frekvensområdet 14-40 GHz vid Onsala rymdobservatorium. Simuleringarna är gjorde med eller utan molnvatten i atmosfären. Antennens normaliserAade effektdiagram tillhandahålls också.

Vi har använt atmosfäriska data från ECMWF och bearbetat dem med det öppna mjukvarupaketet ARTS. Detaljer beskrivs i den publicerade artikeln:
Forkman, P, Flygare, J och Elgered, G (2021).
Water Vapour Radiometry in Geodetic Very Long Baseline Interferometry Telescopes:
Assessed Through Simulations, Journal of Geodesy.

Den uppladdade readme.txt -filen ger all nödvändig information.
De tre datafilerna sparas i NetCDF -format (*.nc)
Simulerade signalfördröjningar av mikrovågor och atmosfärens strålningstemperaturer i frekvensområdet 14–40 GHz vid Onsala rymdobservatorium
Keywords: MICROWAVE RADIANCE; geodesy; geodesi; air water vapour concentration; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Other Earth Sciences; Annan geovetenskap; Earth Observation; Jordobservationsteknik